2016
DOI: 10.1038/emi.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression profiles in the brains of mice infected with scrapie agents 139A, ME7 and S15

Abstract: MicroRNA (miRNA) is a class of non-coding endogenous small-molecule single-stranded RNA that regulates complementary mRNA through degradation or translation of the mRNA targets. Usually, miRNAs show remarkable cell and tissues specificity. Recently, alterations in a set of miRNAs in the brains of patients with certain neurodegenerative diseases, including prion diseases, have been reported. In this study, using deep sequencing technology, miRNA expression profiles in the brains of mice infected with scrapie ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A lack of major correlation between regulated miRNAs in sCJD and scrapie-infected mice was detected in high-throughput studies. However, miRNAs: 146a-5p, 342-3p, 142-3p, 26a-5p, 124a-3p (RNA-seq altered and qPCR validated in sCJD) and 338-5p, 18a-3p, 455-5p, 182-5p (RNA-seq altered in sCJD) are commonly altered in at least one of the studies where scrapie miRNA profiles have been investigated [ 21 23 , 25 , 33 , 66 ]. Additionally, two miRNAs upregulated in the basis pontis of bovine spongiform encephalopathy-infected macaques, miRNA-342-3p and miRNA-494-3p [ 23 ], were also enriched in sCJD, but exclusively in the FC region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of major correlation between regulated miRNAs in sCJD and scrapie-infected mice was detected in high-throughput studies. However, miRNAs: 146a-5p, 342-3p, 142-3p, 26a-5p, 124a-3p (RNA-seq altered and qPCR validated in sCJD) and 338-5p, 18a-3p, 455-5p, 182-5p (RNA-seq altered in sCJD) are commonly altered in at least one of the studies where scrapie miRNA profiles have been investigated [ 21 23 , 25 , 33 , 66 ]. Additionally, two miRNAs upregulated in the basis pontis of bovine spongiform encephalopathy-infected macaques, miRNA-342-3p and miRNA-494-3p [ 23 ], were also enriched in sCJD, but exclusively in the FC region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, specific miRNA signatures have been proposed for Alzheimer’s (AD), Parkinson’s (PD) and Huntington’s (HD) disease, as well as for Fronto-temporal dementia (FTD) [ 15 20 ], supporting the idea that miRNA deregulation is a common hallmark of neurodegenerative diseases. While the study of miRNAs in relation to prion pathogenesis has gained experimental momentum since several miRNAs were found to be altered in in vivo and ex vivo models of prion diseases [ 21 25 ], the miRNA signature in sCJD has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Altered miRNA expression has been investigated in animal and cell culture models including: (a) a sCJD mouse model that recapitulates CJD brain neuropathology ( Padilla et al, 2011 ; Llorens et al, 2014 , 2017 , 2018 ), (b) BSE-infected macaques ( Montag et al, 2009 ) (c) murine models intracerebrally inoculated with various scrapie strains [RML ( Majer et al, 2012 ; Boese et al, 2016 ), 139A ( Gao et al, 2016 ), Me7 ( Gao et al, 2016 ) and 22A ( Saba et al, 2008 )] or scrapie infected SMB-S15 cells ( Gao et al, 2016 ), (d) murine hypothalamic GT1-7 cells infected with a mouse adapted human GSS strain ( Bellingham et al, 2012 ; Bellingham and Hill, 2017 ) and (e) murine neuroblastoma cells propagating the 22L scrapie strain ( Montag et al, 2012 ).…”
Section: Mirna Signatures In the Brain Of Prion Diseases-afflicted Inmentioning
confidence: 99%
“…miRNA-125 is upregulated in prion, AD, and PD models ( Cogswell et al, 2008 ; Bellingham et al, 2012 ; Cardo et al, 2013 ). Recently, Gao et al (2017) worked on miRNA expression profile of three prion strains, 139A, ME7, and S15. They found that the most significantly upregulated and downregulated miRNAs in scrapie-infected mice were, mmu-miRNA-3473e (9.48 log 2 ) and mmu-miRNA-141-5p (-7.33 log 2 ) in the 139A group, mmu-miRNA-3473e (13.18 log 2 ) and mmu-miRNA-200a-5p (-7.08 log 2 ) in the ME7 group, and mmu miRNA-3473e (14.15 log 2 ) and mmu-miRNA-183-3p (-10.15 log 2 ) in the S15 group ( Gao et al, 2017 ).…”
Section: Regulation Of Mirnas In Prion Diseasesmentioning
confidence: 99%
“…Recently, Gao et al (2017) worked on miRNA expression profile of three prion strains, 139A, ME7, and S15. They found that the most significantly upregulated and downregulated miRNAs in scrapie-infected mice were, mmu-miRNA-3473e (9.48 log 2 ) and mmu-miRNA-141-5p (-7.33 log 2 ) in the 139A group, mmu-miRNA-3473e (13.18 log 2 ) and mmu-miRNA-200a-5p (-7.08 log 2 ) in the ME7 group, and mmu miRNA-3473e (14.15 log 2 ) and mmu-miRNA-183-3p (-10.15 log 2 ) in the S15 group ( Gao et al, 2017 ). Recently, Burak et al (2018) demonstrated that miRNA-16 localized within the CA1 region of the hippocampus was upregulated in the early stage of prion infection.…”
Section: Regulation Of Mirnas In Prion Diseasesmentioning
confidence: 99%